Statistical localization of human olfactory cortex - Seubert, Janina; Freiherr, Jessica; Djordjevic, Jelena; Lundstroem, Johan N. (NeuroImage, 2013)
Functional neuroimaging methods have been used extensively during the last decades to explore the neural substrates of olfactory processing. While a general consensus on the functional anatomy of olfactory cortex is beginning to emerge, the mechanisms behind the functions of individual processing nodes still remain debated. Further, it remains unclear to which extent divergent findings result from differences in methodological approaches. Using Activation Likelihood Estimation (ALE), the aim of the present study was to statistically combine all published data on functional neuroimaging of olfaction to provide a probability map reflecting the state of the field to date. Additionally, we grouped studies according to various methodological approaches to investigate whether these systematically affected the reported findings. A total of 45 studies (69 contrasts, 594 foci) met our inclusion criteria. Significant ALE peaks for odor against baseline were observed in areas commonly labeled as primary and secondary olfactory cortex, such as the piriform and orbitofrontal cortex, amygdala, anterior insula, and ventral putamen. In addition, differences were observed in the extent to which different methods were able to induce activation in these different nodes of the olfactory network. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Olfaction; Brain imaging; Activation likelihood estimation; Piriform cortex